Dynamic physical education for elementary school children - Dauer, Victor Paul (Burgess Pub. Co., 1983)
Updated to incorporate current standards and recommendations, "the bible" of elementary P.E. continues to provide the best combination of theoretical framework and hands-on activities available. Dynamic Physical Education for Elementary School Children provides prospective teachers with the tools necessary to ensure success in today's educational environment. Whether starting a new program, restructuring an established one, or working with a team in an existing system, DPE is a valuable pre-service and in-service tool. The thirteenth edition integrates the National Standards for Physical Education and addresses new recommendations designed to increase the activity levels of children and improve their overall fitness levels.